The Aftermath of Cyberstalking: School, Work, Social, and Health Costs of Victimization - Fissel, Erica R. (American journal of criminal justice, 2020)
The harms crime victims experience extend far beyond the initial victimization and can have severe negative impacts on daily life. Using data collected via a self-report survey from 477 cyberstalking victims, the current study explores the consequences associated with being cyberstalked. Specifically, we seek to identify which characteristics of the victimization incident, cyberstalker, and victim impact the likelihood of experiencing four types of consequences – those that are school-, work-, social-, and health-related. Findings revealed that dimensions of the incident, along with offender and victim characteristics, were significantly related to experiencing consequences as a result of being cyberstalked. A discussion of these findings and suggestions for future research are provided.